2020
DOI: 10.3390/ijerph17207630
|View full text |Cite
|
Sign up to set email alerts
|

Managing Cystic Fibrosis in Polish Healthcare

Abstract: The quality and length of life of patients with cystic fibrosis (CF) are determined by a number of factors including the quality of healthcare received by patients, as well as access to drug programs dedicated to this particular disease. The purpose of this paper is to present an overview of changes in the average life expectancy and mortality rate of the CF population in Poland between 2000 and 2018. Furthermore, we would like to evaluate access to healthcare services, including the drug program, guaranteed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In our study, the prevalence of CFRD in Poland was 12.9%, which may be defined as average for the purpose of the CFRD prevalence study in different countries [ 24 ]. Nevertheless, Fendler et al noted the increase in the prevalence of CFRD in Poland between 2005 and 2011, which could be a result of the improved care of CF children but also an increased awareness of the disease’s diabetogenic potential and reduced patient mortality [ 3 , 27 ]. Similarly, the Cystic Fibrosis Foundation Patient Registry, which collects data from the United States, reported that the diagnosis of CFRD is becoming more frequent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, the prevalence of CFRD in Poland was 12.9%, which may be defined as average for the purpose of the CFRD prevalence study in different countries [ 24 ]. Nevertheless, Fendler et al noted the increase in the prevalence of CFRD in Poland between 2005 and 2011, which could be a result of the improved care of CF children but also an increased awareness of the disease’s diabetogenic potential and reduced patient mortality [ 3 , 27 ]. Similarly, the Cystic Fibrosis Foundation Patient Registry, which collects data from the United States, reported that the diagnosis of CFRD is becoming more frequent.…”
Section: Discussionmentioning
confidence: 99%
“…They also noted the increase in the number of chronic infections among CFRD patients with age. In our study, the decline in the number of infections after the age of 30 may result from the lower number of patients in this age group due to the mortality of patients and the fact that the average lifespan of CF patients in Poland is 24.5 ± 8.9 years [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cystic fibrosis (CF) is a heterogeneous multiorgan disease caused by mutations in a gene that leads to a defective or missing CF transmembrane conductance regulator. As survival time increases, technological advances and improved quality of health care, there are still significant discrepancies in height, weight, and body mass index (BMI) of patients with CF compared to healthy controls ( 1 , 2 ). Approximately 70% of CF patients suffer from malnutrition, and in some patients, additionally, body weight deficiency, growth deficiency, reduced brachial fold thickness and reduced lean tissue mass are also observed ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary failure is the main cause of death in this population, while heavy involvement of the gastrointestinal system creates significant nutritional deficiencies 5 7 . Today, due to new treatments, as well as increased awareness of the disease, patients with CF live longer so that more than half of those living with CF are adults 8 . Consequently, sexual and reproductive health is increasingly important for people with CF, as many consider parenting.…”
Section: Introductionmentioning
confidence: 99%